In vitro culture of Rumohra adiantiformis spores and subsequent establishment of the prothallus in commerce and in nature : a feasibility study - Leivers, Stephen (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. in Forest Science) -- University of Stellenbosch, 1992.